2021
DOI: 10.3390/cells10082086
|View full text |Cite|
|
Sign up to set email alerts
|

Cell Therapy for Anal Sphincter Incontinence: Where Do We Stand?

Abstract: Anal sphincter incontinence is a chronic disease, which dramatically impairs quality of life and induces high costs for the society. Surgery, considered as the best curative option, shows a disappointing success rate. Stem/progenitor cell therapy is pledging, for anal sphincter incontinence, a substitute to surgery with higher efficacy. However, the published literature is disparate. Our aim was to perform a review on the development of cell therapy for anal sphincter incontinence with critical analyses of its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 135 publications
1
7
0
Order By: Relevance
“…In our study, on day 5, the incisions in the PBS injection group were close to healing. Comparing with previous 25% anal sphincterectomy studies by others at adjacent time points [ 14 , 17 , 44 ], it appeared that the rats in our modeling showed faster healing and tissue sectioning. This may first be due to differences in observation time.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In our study, on day 5, the incisions in the PBS injection group were close to healing. Comparing with previous 25% anal sphincterectomy studies by others at adjacent time points [ 14 , 17 , 44 ], it appeared that the rats in our modeling showed faster healing and tissue sectioning. This may first be due to differences in observation time.…”
Section: Discussionsupporting
confidence: 72%
“…MSC can be derived from various sources [ 10 ] with differences in marker expression profile and differentiation potential [ 11 ]. To date, MSC [ 12 , 13 , 14 ], adipose-derived stem cells (ADSC) [ 15 ], and skeletal muscle-derived stem cells [ 16 ] have been used in preclinical and clinical studies over the past few years [ 17 , 18 , 19 ] and have shown significant therapeutic effects in treating ASI. Williams et al [ 20 ] treated intrinsic urinary sphincter deficiency (ISD) with skeletal muscle precursor stem cells and showed improvement in muscle proportions and urethral function, and the local injection group showed better efficacy than the intravenous injection group.…”
Section: Introductionmentioning
confidence: 99%
“…In 44 studies, MSCs originated from muscle in 28 studies (17 skeletal and 11 smooth), from BM in 10, and from AT in 6. Eight studies used neural cells for bioengineered constructs and one publication used umbilical cord [24].…”
Section: Stem Cell Therapymentioning
confidence: 99%
“…Stem cell therapy is a promising approach to cure degenerative diseases and has been proposed for the treatment of various disease, including anal sphincter incontinence (ASI) [1][2][3]. Despite more than 20 years of research in this field with encouraging preclinical studies and clinical trials, there still is a lack of consensus regarding the cells that should be used [1][2][3][4]. In the literature, two candidates emerged for clinical application: muscular tissue-derived stem cells (M-SCs) (satellite cells or myoblasts) and adipose-tissue derived stem cells (A-SCs) [3].…”
Section: Introductionmentioning
confidence: 99%